2022
DOI: 10.3389/ijph.2022.1604272
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Health Literacy in Romania: Validation of the HLS-EU-Q16 Survey Questionnaire

Abstract: Objective: Empirical data on health literacy (HL) for Romania is almost inexistent. The present study aimed to validate the HLS-EU-Q16 questionnaire for the Romanian population and explore the predictors of HL in the North-West Region of the country.Methods: A non-experimental, cross-sectional study was conducted between March and November 2019 on a representative, stratified random sample of 1,622 participants from the North-Western Region of Romania. Exploratory Factor Analysis (EFA), Principal component ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
3
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
1
8
3
5
Order By: Relevance
“…Factor 1 focuses on measuring active search, understanding, and use of information provided by health personnel, while factor 2 reflects the ability to judge information on self-care and disease prevention originating from media and friends. This finding contrasts with observations reported in other studies: in Spain, 19 the researchers found that the scale is unifactorial, while in Romania and Iceland four factors were identified, 20,21 and in Turkey, three. 22 These discrepancies indicate that the health literacy domains implicit in the scale do not manifest themselves equally between different cultures.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Factor 1 focuses on measuring active search, understanding, and use of information provided by health personnel, while factor 2 reflects the ability to judge information on self-care and disease prevention originating from media and friends. This finding contrasts with observations reported in other studies: in Spain, 19 the researchers found that the scale is unifactorial, while in Romania and Iceland four factors were identified, 20,21 and in Turkey, three. 22 These discrepancies indicate that the health literacy domains implicit in the scale do not manifest themselves equally between different cultures.…”
Section: Discussioncontrasting
confidence: 99%
“…When HLS-EU-Q16 was validated in our population, 12 out of 16 questions were retained, and, for this reason, the literacy scale in Mexico is referred to as HLS-EU-Q12M. Our results differ from those obtained in Spain, 19 Romania, 20 Iceland 21 and Turkey, 22 given that, when the questionnaire was applied to the general population in those countries, no question was eliminated. One possible explanation is that the questions that were eliminated were those with the highest percentages of "I don't know" answers.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Therefore, the HLS-EU-Q16 was developed based on the data of the 8 original HLS-EU countries [ 10 , 11 , 15 , 16 , 17 ] and further validated for two additional studies in CZ and HU [ 10 ], an Austrian study of adolescents [ 10 , 18 ] and an Austrian study on two groups of migrants [ 10 , 19 , 20 ]. Later studies validating or applying the instruments in further languages were published: in Swedish and Arabic [ 21 ], in Somali [ 22 ], in Arabi, Dari, and Somali [ 23 ], in Italian [ 24 , 25 ], in Indonesian [ 26 ], in Austrian German [ 27 ], in French [ 28 , 29 ], in Turkish [ 30 ], in Japanese [ 31 ], in Islandic [ 32 ], in Romanian [ 33 ], and in an adapted Q18 version in Malaysian [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…the HLS-EU-Q16 and the HLS-EU-Q6 (which consists of 16 respectively six items from the original HLS-EU-Q) [7]. The HLS-EU-Q16 has been translated into several languages and psychometrics tests show that the validity of most of the translated versions are satisfactory [8][9][10][11][12][13][14], only the Japanese version has shown weak validity [15]. Arabic is the sixth most common language worldwide [16] and the language that most migrants with a refugee background speak [17].…”
mentioning
confidence: 99%